Carotid artery dissection causing hypoglossal nerve palsy. (28th June 2012) - Epstein, Elliot; Khan, Muhammed Azeem; Francis, David; Sada, Priyo; Thuse, Makarand
Abstract : A 45-year-old man was admitted with a 4 day history of right facial pain and on examination, there was atrophy of the right side of the tongue. Magnetic resonance angiography demonstrated carotid artery dissection and aspirin was commenced.